Semantic Web Technologies for Enterprise 2.0. - Passant, A. (IOS Press, 2010)
Of these Two VisionsWeb 2.0 Assets for the Semantic Web; Semantic Web Assets for Web 2.0; Conclusion; Chapter 2. SemSLATES: A Semantic Approach for Enterprise 2.0; Introduction; Collaboration in the Enterprise: the Athena Project; Motivations and Goals; The Hermes Platform; RSS for Information Integration and Sharing; Weblogs for Content Publishing; Wikis for Collaborative Knowledge Management; Document Annotation and Information Retrieval; Overall Integration of the Services; Usage Statistics; Issues of Enterprise 2.0 Ecosystems.